Organic Chemistry - Morrison, Robert Thornton; Boyd, Robert Neilson (New Delhi : Pearson Education, 2007)
In the time since the sixth edition of this best seller by Morrison and Boyd was published in 1992, organic chemistry has witnessed a metamorphosis, both in the methods of synthesis and in the analysis of organic compounds. This seventh edition is revised as per the developments that have been taken place in the field of organic chemistry as well as in the syllabi. As in the early editions, the book conveys the important fundamentals and principles of the subject in a simple and easily understandable manner.
includes index.
Keywords: Organic Chemistry